2021
DOI: 10.1016/j.jmmm.2020.167386
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-induced phase transition in metal dichlorides XCl2 (X: Fe, Co, and Ni)

Abstract: We investigated the ground state of monolayer 1T-XCl2 (X: Fe, Co, and Ni) using the generalized Bloch theorem, which can generate ferromagnetic, spiral, and antiferromagnetic states. Each state was represented by a unique spiral vector that arranges the magnetic moment of magnetic atom in the primitive unit cell. We found the ferromagnetic ground state for the FeCl2 and NiCl2 while the spiral ground state appears for the CoCl2. We also showed that the ground state depends sensitively on the lattice constant. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…We find a half-metallic property for the unstrained case (𝜖 = 0%), in a good agreement with Ref. [2][3][4][5][6]. As the compressive strain is applied with 𝜖 = −8%, we observe the metallic properties for both spin states, thus changing from half-metallic state to the semiconducting state, as shown in Fig 2(c).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…We find a half-metallic property for the unstrained case (𝜖 = 0%), in a good agreement with Ref. [2][3][4][5][6]. As the compressive strain is applied with 𝜖 = −8%, we observe the metallic properties for both spin states, thus changing from half-metallic state to the semiconducting state, as shown in Fig 2(c).…”
Section: Resultssupporting
confidence: 88%
“…In the FeCl2 monolayer, the magnetic property is governed by the ferromagnetic super-exchange to ensure the ferromagnetic ground state [4]. However, the doping and Coulomb repulsion can change this state to the other states [5][6][7][8]. One of the interesting properties in the FeCl2 monolayer is the half-metallic property.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the calculated local moment of the NiBr2 monolayer in the unit cell is about 1.32 μB. Note that this very is also very close with NiBr2 [13] and NiBr2 [14]. When the spin-orbit interaction is included, it reduces the energy gap at the Γ point in the CBM and VBM.…”
Section: Resultssupporting
confidence: 55%
“…Here, the total energy difference ∆𝐸 = 𝐸 AFM − 𝐸 FM and magnetic moment M are described. Notice that the most stable state of FeCl2 monolayer is an FM state [16]. In addition, it is also observed that the magnetic moment increases as U increases.…”
Section: Resultsmentioning
confidence: 77%